Parity: An Intuitive Case. (December 2016) - Chang, Ruth
Abstract: In other work I have argued that items can be on a par, where being on a par is a fourth, basic, sui generis value relation beyond the usual trichotomy of 'better than', 'worse than', and 'equally good'. In this paper, I aim to marshal non‐technical, intuitive arguments for this view. First, I try to cast doubt on the leading source of intuitive resistance to parity, the conviction that if two items are comparable, one must be better than the other, worse than it, or they must be equally good. Second, I explain how parity can arise by appealing to an uncontroversial distinction between quantity and quality of value. I propose both sufficient conditions for parity and a nontechnical model of the notion. My overall aim is to bring into view a simple and intuitive picture of value – and more generally of normativity – in which parity plays a significant role.